2020
DOI: 10.3892/mmr.2020.11670
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation of bone: Role of different peptides and their interactions (Review)

Abstract: Our understanding of the skeletal system has been expanded upon the recognition of several neural pathways that serve important roles in bone metabolism and skeletal homeostasis, as bone tissue is richly innervated. Considerable evidence provided by in vitro, animal and human studies have further elucidated the importance of a host of hormones and local factors, including neurotransmitters, in modulating bone metabolism and osteo-chondrogenic differentiation, both peripherally and centrally. Various cells of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 139 publications
(300 reference statements)
0
16
0
Order By: Relevance
“…Neuropeptides are involved in the regulation of bone metabolism, influencing the activity of bone cells, including osteoblasts, osteoclasts, and osteocytes [ 1 , 2 , 34 , 35 ]. Nevertheless, the role in bone of opioids, a specific class of neuropeptides, is still partially unclear and the complexity of their signalling pathway further complicates the scenario.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropeptides are involved in the regulation of bone metabolism, influencing the activity of bone cells, including osteoblasts, osteoclasts, and osteocytes [ 1 , 2 , 34 , 35 ]. Nevertheless, the role in bone of opioids, a specific class of neuropeptides, is still partially unclear and the complexity of their signalling pathway further complicates the scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that neuropeptides affect the functions of bone cells playing an essential role in the metabolism of the skeletal tissues [ 1 , 2 ]. Pre-proenkephalin 1 ( Penk1 ) is a gene encoding a pro-neuropeptide that is proteolytically processed to generate the following enkephalins: [Met]-enkephalin, [Met]-enkephalin extended sequence, and [Leu]-enkephalin, all belonging to the family of opioid peptides that are endogenous ligands for opioid receptors having potent analgesic properties [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…49 Furthermore, sensory nerve fibers are more densely innervated in the epiphysis compared to the metaphysis, and are mainly restricted to vascularized CD31 + Haversian canals. 1,50 Sensory nerves can be classified by their receptors and channels, such as toll-like receptors, tyrosine kinase receptors, transient receptor potential ion channels, and mechanosensitive Piezo channels. 44,51 These receptors and channels initiate intracellular signaling and the release of neuropeptides.…”
Section: Sensory Afferents Mediate Interoceptive Signals To Facilitat...mentioning
confidence: 99%
“…Neuropeptides impact a large and diverse array of physiological processes (Insel, 2010; Mills et al, 2020; Neumann & Landgraf, 2012; Steinhoff et al, 2014; Wang et al, 2021; Xu et al, 2020). Functional elucidation is not trivial notably due to neuropeptide co‐transmission capabilities (Nusbaum et al, 2017) and pleiotropic nature (Souza‐Moreira et al, 2011).…”
Section: Functional Studiesmentioning
confidence: 99%